Interface between jurisdiction instruments and arbitration - Dowers, Neil Alexander (The University of Edinburgh, 2015)
This thesis addresses the question of how conventions and other instruments regulating court jurisdiction should deal with court proceedings relating to arbitration. It argues that the conventional approach of excluding court proceedings related to arbitration entirely from the scope of the jurisdiction instrument cannot be justified with reference to any international arbitration convention. It continues to argue that the exclusion of arbitration causes or exacerbates significant problems at the interface between the courts and arbitration, taking the European Union’s recent experience as an example. It then argues that the European legislature has recently directly considered the exclusion of arbitration from its jurisdictional instruments and failed to act effectively. Any amendments to this system will necessarily be offered within the relevant legal context, so an assessment of the prevailing principles in European international private law and international commercial arbitration will follow. Furthermore, the ongoing debate surrounding the delocalisation of arbitration and its relevance to the debate about the interface between court jurisdiction and arbitration shall be addressed. Finally, this thesis proposes a model for inclusion of arbitration in the European jurisdiction instrument (the Brussels I Regulation) that would, it is argued, solve or ameliorate the problems at the interface between the Regulation and arbitration, whilst broadly aligning with the prevailing principles in the relevant legal context. The thesis then considers whether this approach could be extended beyond Europe to the world at large, concluding that it could not. This work therefore takes an original approach to a topic of much contemporary controversy, by taking a holistic, rounded, and reasoned view of the problems at the interface between court jurisdiction and arbitration. It also contains original insights into several other areas, including the historical justification for the exclusion of arbitration from jurisdiction conventions, the importance of mutual trust as a founding principle of the common market, the relevance of the delocalisation debate to the topic, and the proposal for reform advanced at the end of this thesis.
Keywords: arbitration; international private law; jurisdiction